2013
DOI: 10.1002/pmic.201200562
|View full text |Cite
|
Sign up to set email alerts
|

Proteome profiling of exosomes derived from human primary and metastatic colorectal cancer cells reveal differential expression of key metastatic factors and signal transduction components

Abstract: Exosomes are small extracellular 40-100 nm diameter membrane vesicles of late endosomal origin that can mediate intercellular transfer of RNAs and proteins to assist premetastatic niche formation. Using primary (SW480) and metastatic (SW620) human isogenic colorectal cancer cell lines we compared exosome protein profiles to yield valuable insights into metastatic factors and signaling molecules fundamental to tumor progression. Exosomes purified using OptiPrep™ density gradient fractionation were 40-100 nm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
274
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(299 citation statements)
references
References 103 publications
19
274
1
5
Order By: Relevance
“…cholesterol and ceramide), membrane fusion-related proteins (Rab GTPases, flotillins and connexins), proteins involved in vesicle formation (Alix, Tsg 101), integral membrane proteins such as tetraspanins (CD9, CD63, CD 81) and major histocompatibility complex (MHC) class I and II as well as proteins related to the cytoskeleton and the cell metabolism have been identified (16). Also proteins involved in the pathogenesis of cancer such as oncoproteins MET and mutant KRAS have been found in exosomes (17,18). As nucleic acidrelated cargo, mRNA, miRNA, long non-coding RNAs as well as DNA have been detected (19).…”
Section: General Features Of Exosomesmentioning
confidence: 99%
“…cholesterol and ceramide), membrane fusion-related proteins (Rab GTPases, flotillins and connexins), proteins involved in vesicle formation (Alix, Tsg 101), integral membrane proteins such as tetraspanins (CD9, CD63, CD 81) and major histocompatibility complex (MHC) class I and II as well as proteins related to the cytoskeleton and the cell metabolism have been identified (16). Also proteins involved in the pathogenesis of cancer such as oncoproteins MET and mutant KRAS have been found in exosomes (17,18). As nucleic acidrelated cargo, mRNA, miRNA, long non-coding RNAs as well as DNA have been detected (19).…”
Section: General Features Of Exosomesmentioning
confidence: 99%
“…For testing exosomes at the in situ protein level, we selected the ALG 2-interacting protein X (ALIX; also known as programmed cell death 6-interacting protein (PDCD6IP)), a multifunctional protein, which is involved in biogenesis of MVBs (as ESCRT I-III binding protein), lysosomal degradation and accumulates in exosomes. 3,[25][26][27] ALIX has been tested widely in exosome studies of colorectal carcinoma cell cultures 9,28 and has shown diagnostic and prognostic significance in different tumors. [29][30][31] Besides testing the transcript levels, here we determined ALIX protein expression in situ in the epithelial and stromal compartment including α-smooth muscle actin (SMA)-positive cells in low-and high-grade dysplastic adenomas as well as non-metastatic and metastatic (both lymph node and distant) colorectal carcinomas with particular focus on individual Musashi1-positive cancer stem cells at the tumor front.…”
mentioning
confidence: 99%
“…Cell-free nucleic acid has been identified in stable protein complexes, as well as encapsulated in microvesicles and exosomes (23)(24)(25). Exosomes are small (50-100 nm) vesicles that carry a unique composition of proteins (26), lipids (27), mRNA (28), and miRNA (29). Exosomes form in the endosomal multivesicular bodies of the cytoplasm of various cell types and are secreted into body fluids, including blood plasma (30).…”
mentioning
confidence: 99%